Secondary battery and electronic device

By designing specific structures on the separator and electrode sheet of the secondary battery, including the bonding layer and the trunking groove, the problem of electrolyte difficulty in penetrating into the electrode sheet is solved, and the circulation and fast charging performance of the secondary battery are significantly improved.

CN119650812APending Publication Date: 2025-03-18NINGDE AMPEREX TECHNOLOGY LTD
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411844323.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

When existing secondary batteries are charged at high speed at high current, it is difficult for the electrolyte to completely penetrate into the inner layer of the electrode sheet, resulting in deterioration of circulation and fast charging performance.

Method used

A secondary battery including a separator and a pole sheet is designed. An adhesive layer is provided in the separator and composed of a plurality of bonding points. The thickness of the bonding layer is 0.5 μm to 5 μm. An active layer is provided on the pole sheet. Part of the active layer is recessed inward to form several etching grooves.

Benefits of technology

By improving the structure of the separator and pole sheet, the transmission and storage capacity of the electrolyte is enhanced, and the circulation and fast charging performance of the secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650812A_ABST
    Figure CN119650812A_ABST
Patent Text Reader

Abstract

The invention provides a secondary battery comprising a diaphragm and a pole piece and an electronic device. The diaphragm in the secondary battery comprises a base film layer, at least one surface of the base film layer is provided with a bonding layer, the bonding layer is composed of a plurality of bonding points, and the thickness of the bonding layer is 0.5-5 [mu] m; in the bonding layer, the longest diameter of a bonding point is 10 [mu] m-400 [mu] m, and the distance between adjacent bonding points is 100 [mu] m-400 [mu] m. The pole piece of the secondary battery comprises a current collector, at least one surface of the current collector is provided with an active layer, a partial area of the surface of the active layer is recessed inwards to form a plurality of scribed grooves, and the scribed grooves are arranged along the length direction of the pole piece; the width of the scribing groove is D1 mm, and 0.2 < = D1 < = 1.5. The diaphragm and the pole piece provided by the invention have good electrolyte transmission capability and storage capability, and can enhance the cycle performance and fast charge performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of energy storage, and in particular to a secondary battery and an electronic device. Background Art

[0002] As the energy density of secondary batteries continues to increase, the compaction density requirements and coating surface density requirements for battery pole pieces are becoming increasingly higher. This results in the transmission of electrolyte in the pole piece becoming an obstacle to improving the fast charging performance and long cycle performance of the battery. The electrolyte is difficult to completely penetrate into the inner layer of the pole piece. At the same time, the pole piece's ability to store electrolyte is also reduced, resulting in the formation of a concentration gradient of lithium ions inside the secondary battery during use, resulting in concentration polarization, and causing deterioration of the secondary battery's cycle performance and fast charging performance. Summary of the invention

[0003] The present application can provide a secondary battery and an electronic device including a diaphragm and a pole piece. The diaphragm and the pole piece in the secondary battery of the present application have good electrolyte transmission and storage capabilities, and can enhance the cycle performance and fast charging performance of the secondary battery.

[0004] In the first aspect, the present application provides a secondary battery, which includes a diaphragm and a pole piece, the diaphragm includes a base film layer, at least one surface of the base film layer is provided with an adhesive layer, the adhesive layer is composed of a plurality of adhesive points, and the thickness of the adhesive layer is 0.5 μm to 5 μm; in the adhesive layer, the longest diameter of the adhesive points is 10 μm to 400 μm, and the distance between adjacent adhesive points is 100 μm to 400 μm. The secondary battery also includes a pole piece, which includes a current collector, at least one surface of the current collector is provided with an active layer, and a surface area of ​​the active layer is inwardly concave to form a plurality of grooves, and the grooves are arranged along the length direction of the pole piece; the width of the grooves is D1 mm, 0.2≤D1≤1.5.

[0005] Based on the diaphragm of the present application, the inventors found that since the bonding layer in the diaphragm is composed of bonding points of 10μm to 400μm, and the distance between adjacent bonding points is 100μm to 400μm, an electrolyte transmission channel can be formed in the bonding layer, and the bonding points not only have good bonding ability, but also have good liquid storage capacity. When at least one surface of the current collector of the pole piece in the secondary battery is provided with an active layer, a portion of the surface area of ​​the active layer is recessed inward to form a number of grooves, and the grooves are arranged along the length direction of the pole piece; the width of the groove is D1mm, 0.2≤D1≤1.5, when the pole piece meets these conditions, the adaptation between the pole piece and the diaphragm can improve the battery performance of the secondary battery under high-speed charging with large current, and improve the lithium precipitation of the secondary battery. Therefore, the secondary battery of the present application has good electrolyte transmission capacity and electric energy storage capacity, and the cycle performance and fast charging performance of the secondary battery can be improved.

[0006] In one embodiment of the present application, the longest diameter of the bonding points is 10 μm to 200 μm; and / or the distance between adjacent bonding points is 150 μm to 300 μm.

[0007] Based on the above implementation scheme, the diaphragm has a stronger electrolyte transmission capability and a stronger liquid storage performance.

[0008] In one embodiment of the present application, the thickness of the adhesive layer is 1 μm to 3 μm.

[0009] Based on the above implementation scheme, the separator that meets the requirements of the present application can be used in a secondary battery to further improve the cycle performance and fast charging performance of the secondary battery.

[0010] In one embodiment of the present application, the spacing between adjacent grooves is D2 mm, 1≤D2≤3. The fast charging performance of the secondary battery can be improved, and the lithium plating phenomenon of the secondary battery can be improved.

[0011] In one embodiment of the present application, the adhesive layer includes a water-based polymer, and the polymerization monomers of the water-based polymer include at least two of butadiene, methyl acrylate, methyl methacrylate, styrene, butyl methacrylate, isooctyl acrylate, ethylene, propylene or vinylidene fluoride.

[0012] Based on the above implementation scheme, the water-based polymer itself has good bonding properties, and the main chain and side chain of the water-based polymer can be additionally grafted with a binder, which is beneficial to improving the bonding strength of the bonding layer.

[0013] In one embodiment of the present application, the electrode sheet is a negative electrode sheet, which can improve the wetting of the negative electrode sheet with the electrolyte, thereby increasing the liquid storage capacity of the negative electrode sheet, which is beneficial to improving the cycle performance and fast charging performance of the secondary battery.

[0014] Based on the above-mentioned pole piece, the groove can not only play a drainage role, allowing the electrolyte to flow along the groove, but also play a role in retaining the electrolyte. Therefore, the pole piece of the present application has good electrolyte transmission and storage capabilities, which is conducive to improving the cycle performance and fast charging performance of the secondary battery.

[0015] In one embodiment of the present application, the thickness of the active layer is H1 μm, the depth of the groove is H2 μm, and 0.1≤H2 / H1≤0.3.

[0016] Based on the above implementation scheme, when the depth of the groove and the thickness of the active layer meet the above relationship, the electrode not only has a good liquid storage capacity, but also is not prone to lithium deposition.

[0017] In one embodiment of the present application, the projected area of ​​all the scored grooves on the surface of the current collector is 10% to 20% of the surface area of ​​the current collector.

[0018] Based on the above implementation scheme, the density of the grooves is relatively moderate, and when the pole piece is used in a secondary battery, the energy density of the secondary battery is not easily lost.

[0019] In one embodiment of the present application, the secondary battery includes an electrolyte, a diaphragm, and a pole piece, and the diaphragm and the pole piece are alternately stacked; or the secondary battery includes an electrolyte, a diaphragm, and the above-mentioned pole piece, and the diaphragm and the pole piece are alternately stacked; or the secondary battery includes an electrolyte, the above-mentioned diaphragm, and the pole piece, and the diaphragm and the pole piece are alternately stacked. Therefore, the secondary battery of the present application has good cycle performance and fast charging performance.

[0020] In one embodiment of the present application, the area between adjacent score grooves is a bonding area, and the bonding point is located in the bonding area.

[0021] Based on the above implementation scheme, the bonding points in the diaphragm will not fall into the scored grooves, so the scored grooves can play a good role in transmitting and storing electrolyte, which is beneficial to further improve the cycle performance and fast charging performance of the secondary battery.

[0022] In a second aspect, the present application provides an electronic device, which includes the above-mentioned secondary battery.

[0023] Based on the above implementation scheme, the cycle performance and fast charging performance of the secondary battery are better.

[0024] Beneficial effects of this application:

[0025] The present application provides a secondary battery including a diaphragm and a pole piece, wherein the diaphragm includes a base film layer, and at least one surface of the base film layer is provided with an adhesive layer, the adhesive layer is composed of a plurality of adhesive points, and the thickness of the adhesive layer is 0.5 μm to 5 μm; in the adhesive layer, the longest diameter of the adhesive points is 10 μm to 400 μm, and the distance between adjacent adhesive points is 100 μm to 400 μm. Since the diaphragm of the secondary battery of the present application has a transmission channel in the adhesive layer, the diaphragm has good performance in transmitting and storing electrolyte. The pole piece includes a current collector, and at least one surface of the current collector is provided with an active layer, and a surface part of the active layer is inwardly concave to form a plurality of grooves, and the grooves are arranged along the length direction of the pole piece; the width of the grooves is D1 mm, 0.2≤D1≤1.5, and the spacing between adjacent grooves is D2 mm, 1≤D2≤3. Since the pole piece of the secondary battery of the present application contains grooves, the pole piece has good performance in transmitting and storing electrolyte. The secondary battery of the present application can improve the cycle performance and fast charging performance of the secondary battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a demonstration diagram of the electrolyte transmission rate test of the embodiment of the present application;

[0028] Figure 2 This is a CCD image of the bonding layer in Example 1-1 of the present application;

[0029] Figure 3 This is the positive electrode plate in Example 1-1 of the present application. DETAILED DESCRIPTION

[0030] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below. Obviously, the described embodiments are only a part of embodiments of the present application, rather than all embodiments. All other embodiments obtained by those skilled in the art based on the present application belong to the scope of protection of the present application. Those who do not specify specific conditions in the embodiments are carried out according to the conditions recommended by normal conditions or manufacturers. Those who do not specify the manufacturer for reagents or instruments used are conventional products that can be obtained by commercial purchase.

[0031] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.

[0032] At present, in order to improve the energy density of secondary batteries to meet the needs of use, the compaction density of the pole piece is continuously increased, but this is not conducive to the penetration of the electrolyte, thereby affecting the cycle performance and fast charging performance of the secondary battery. Based on this, the present application provides a diaphragm, a pole piece and a secondary battery. The diaphragm and pole piece of the present application have good electrolyte transmission capacity and storage performance. When used in a secondary battery, the cycle performance and fast charging performance of the secondary battery can be improved. The technical solution of the present application is described in detail below.

[0033] In a first aspect, the present application provides a secondary battery, wherein the secondary battery of the present application comprises a separator, which comprises a base film layer, at least one surface of the base film layer is provided with a bonding layer, the bonding layer is composed of a plurality of bonding points, the thickness of the bonding layer is 0.5 μm to 5 μm, preferably 1 μm to 3 μm, for example, it can be 0.5 μm, 0.8 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, etc. or within a range consisting of any two of the above values; in the bonding layer, the longest diameter of the bonding point is 10 μm to 400 μm. The distance between adjacent bonding points is 100 μm to 400 μm, preferably 150 μm to 300 μm, for example, 10 μm to 200 μm, for example, 10 μm, 50 μm, 100 μm, 200 μm, 300 μm, 400 μm, etc., or within the range consisting of any two of the above values. The distance between adjacent bonding points is 100 μm to 400 μm, preferably 150 μm to 300 μm, for example, 100 μm, 120 μm, 150 μm, 250 μm, 300 μm, 350 μm, 400 μm, etc., or within the range consisting of any two of the above values. The present application has no particular limitation on the shape of the bonding points, as long as the purpose of the present application can be achieved.

[0034] It should be noted that the "longest diameter of the bonding point" in this application is relative to the projection shape of the bonding point in the base film layer, and refers to the distance between the two points farthest apart in the projection shape; specifically, when the projection shape of the bonding point is a circle, the "longest diameter" refers to the diameter of the circle; when the projection shape is a ring, the "longest diameter" refers to the radius of the large circle of the ring; when the projection shape is an ellipse, the "longest diameter" refers to the length of the major axis of the ellipse; when the projection shape is a square or a rectangle, the "longest diameter" refers to the length of the diagonal of the square or rectangle. In addition, the "distance between adjacent bonding points" in this application is also relative to the projection shape, and refers to the distance between the projections of two adjacent bonding points, which is the distance between the closest parts of the two projections.

[0035] It should also be noted that in the present application, "at least one surface of the base film layer is provided with an adhesive layer" means that the adhesive layer can be provided on one surface in the thickness direction of the base film layer, or on two surfaces in the thickness direction of the base film layer. The present application has no particular limitation on this, as long as the purpose of the present application can be achieved.

[0036] The inventors found that since the bonding layer in the diaphragm is composed of bonding points of 10μm to 400μm, and the distance between adjacent bonding points is 100μm to 400μm, an electrolyte transmission channel can be formed in the bonding layer, and the bonding points not only have good bonding ability but also have good liquid storage capacity. Therefore, the diaphragm of the present application has good electrolyte transmission capacity and storage capacity, and when used in secondary batteries, it can enhance the cycle performance and fast charging performance of secondary batteries.

[0037] In some embodiments of the present application, in order to make the bonding layer have better bonding properties, the bonding layer includes a water-based polymer, and the polymerized monomers of the water-based polymer include at least two of butadiene, methyl acrylate, methyl methacrylate, styrene, butyl methacrylate, isooctyl acrylate, ethylene, propylene or vinylidene fluoride. The main chain and side chain of the water-based polymer can also be additionally grafted with a binder, which is beneficial to improving the bonding force of the bonding layer. In addition, the inventors also tested the swelling properties of the water-based polymer and found that when the equivalent particle size of the bonding beads formed by the water-based polymer is in the range of 0.2μm to 3μm, the glass transition temperature of the adhesive film prepared using the bonding beads is in the range of 40℃ to 55℃, and the film is immersed in an electrolyte environment, and the swelling rate is stored at 60℃ for 6 hours and 24 hours in the range of 40% to 60% and 60% to 80%, respectively, which shows that the bonding properties of the water-based polymer are good, and the volume change after liquid storage is low, so it is less likely to block the electrolyte transmission channel in the diaphragm.

[0038] The present application has no particular restrictions on the material and thickness of the base film layer in the separator, as long as the purpose of the present application can be achieved. For example, the material of the separator includes, but is not limited to, non-woven fabrics, woven fabrics, microporous membranes, and the like.

[0039] In addition, the present application generally adopts a coating method to prepare the bonding layer in the diaphragm, and the coating equipment selects one of gravure, micro-gravure, screen printing, and extrusion coating. In order to more conveniently control the number, spacing, and size of bonding points, as an example, the bonding layer is prepared by screen printing coating in the specific embodiment of the present application. When using this method, the number, spacing, and size of bonding points in the bonding layer can be changed by replacing screen printing plates with different mesh sizes.

[0040] In the second aspect, the secondary battery of the present application includes a pole piece, which includes a current collector, and an active layer is provided on at least one surface of the current collector. Partial surface area of ​​the active layer is recessed inward to form a plurality of scored grooves, and the scored grooves are arranged along the length direction of the pole piece; the width of the scored grooves is D1mm, 0.2≤D1≤1.5, and the spacing between adjacent scored grooves is D2mm, 1≤D2≤3.

[0041] It should be noted that the above-mentioned pole piece can be either a positive pole piece or a negative pole piece. When it is a positive pole piece, the current collector is a positive current collector and the active layer is a positive active layer; when it is a negative pole piece, the current collector is a negative current collector and the active layer is a negative active layer. However, in actual operation, the positive pole piece is generally provided with a groove. For the convenience of description, this application will not be described separately for positive and negative pole pieces.

[0042] It should also be noted that in the present application, "at least one surface of the current collector is provided with an active layer" means that the active layer can be provided on one surface in the thickness direction of the current collector, or on two surfaces in the thickness direction of the current collector. The present application has no particular limitation on this, as long as the purpose of the present application can be achieved.

[0043] In the pole piece of the present application, the grooves can not only play a drainage role, allowing the electrolyte to flow along the grooves, but also play a role in retaining the electrolyte, so that the pole piece has good electrolyte transmission and storage capabilities, which is conducive to improving the cycle performance and fast charging performance of the secondary battery. Moreover, within the scope specified in the present application, the greater the depth and width of the grooves, the stronger the ability to retain the electrolyte.

[0044] Since the arrangement of the grooves on the active layer will cause the loss of substances in the active layer, it may affect the energy density of the pole piece and the secondary battery. Therefore, in some embodiments of the present application, the projected area of ​​all the grooves on the current collector surface is 10% to 20% of the current collector surface area. In this way, the density of the grooves is relatively moderate, and it is not easy to lose the energy density of the secondary battery. It should be noted that the "projected area of ​​all the grooves on the current collector surface" is calculated based on the projected area of ​​the grooves in all the active layers of the pole piece on the current collector surface, that is, first determine the projected area of ​​the grooves in one of the active layers on the current collector surface, and then determine the projected area of ​​the grooves in another active layer on the current collector surface, and then add the two together; if there is only one active layer in the pole piece, the projected area of ​​the grooves in the active layer on the current collector surface is the projected area of ​​all the grooves in the pole piece on the current collector surface.

[0045] In addition, in some embodiments of the present application, the thickness of the active layer is H1μm, the depth of the groove is H2μm, and 0.1≤H2 / H1≤0.3. If the depth of the groove is too deep relative to the thickness of the active layer, this will require high consistency in the laser etching process, and it is easy to expose the current collector, which may cause lithium precipitation, which is not conducive to the electrical performance of the secondary battery; if the depth of the groove is too shallow relative to the active layer, it may result in less electrolyte being introduced, and the interface cannot be significantly improved, and the cycle performance and fast charging performance of the secondary battery are not significantly improved.

[0046] Next, the positive electrode and the negative electrode are described in detail:

[0047] Positive electrode

[0048] In the positive electrode sheet, the components of the positive electrode active layer include positive electrode active materials, which can be any material that can reversibly embed and de-embed Li + 、Na +For example, the positive electrode active material includes but is not limited to at least one of lithium iron phosphate (LiFePO4), lithium cobalt oxide (LiCoO2), lithium manganese oxide, lithium nickel oxide, ternary materials, etc., and the ternary materials include but are not limited to LiNi x Co y Mn z O2、LiNi x Co y Al z O2, etc., and the content of Ni, Co, Mn, Al, etc. can be adjusted to ensure that x+y+z=1. For example, the ternary material can be LiNi 0.6 Co 0.2 Mn 0.2 O2、LiNi 0.88 Co 0.08 Mn 0.04 O2、LiNi 0.8 Co 0.15 Mn 0.05 O2、LiNi 0.8 Co 0.1 Mn 0.1 O2、LiNi 0.88 Co 0.1 Mn 0.02 O2、LiNi 0.8 Co 0.15 Al 0.05 O2、LiNi 0.88 Co 0.1 Al 0.02 O2, etc.

[0049] In some embodiments of the present application, the components of the positive electrode active layer also include a positive electrode conductive agent; the present application has no restrictions on the type of the positive electrode conductive agent, and any known conductive material can be used. Specifically, the positive electrode conductive agent includes, but is not limited to, at least one of acetylene black, Super-P and other carbon blacks, or amorphous carbon materials such as needle coke, or carbon nanotubes, or graphene, etc.

[0050] In some embodiments of the present application, the components of the positive electrode active layer generally also contain a positive electrode binder. There is no particular restriction on the type of positive electrode binder used in the manufacture of the positive electrode active layer. In the case of a coating method, any material that can be dissolved or dispersed in the liquid medium used in electrode manufacturing can be used. The positive electrode binder includes, but is not limited to, any one or at least two of the following: resin polymers such as polyethylene, polypropylene, polyethylene terephthalate, polymethyl methacrylate, polyimide, aromatic polyamide, cellulose, and nitrocellulose; rubber polymers such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), fluororubber, isoprene rubber, polybutadiene rubber, and ethylene-propylene rubber; thermoplastic elastomer polymers such as styrene-butadiene-styrene block copolymers or their hydrides, ethylene-propylene-diene terpolymers (EPDM), styrene-ethylene-butadiene-ethylene copolymers, styrene-isoprene-styrene block copolymers or their hydrides; soft resin polymers such as isotactic-1,2-polybutadiene, polyvinyl acetate, ethylene-vinyl acetate copolymers, and propylene-α-olefin copolymers; fluorine-based polymers such as polyvinylidene fluoride (PVDF), polytetrafluoroethylene, fluorinated polyvinylidene fluoride, and polytetrafluoroethylene-ethylene copolymers; polymer compositions having ion conductivity of alkali metal ions (especially lithium ions), etc.

[0051] In the positive electrode sheet, the type of positive current collector is not particularly limited, and it can be any material known to be suitable for use as a positive current collector. The material of the positive current collector includes, but is not limited to, metal materials such as aluminum, stainless steel, nickel plating, titanium, tantalum, and materials such as carbon cloth and carbon paper. In addition, in order to reduce the electronic contact resistance between the positive current collector and the positive active layer, a conductive additive or a conductive coating may be provided on the surface of the positive current collector. Conductive additives include, but are not limited to, carbon and precious metals such as gold, platinum, and silver. The conductive coating may be a mixture layer of an inorganic oxide, a conductive agent, and a positive electrode binder.

[0052] When preparing the positive electrode sheet, the components in the above-mentioned positive electrode active layer can be dissolved or dispersed in a liquid solvent to prepare a positive electrode slurry, and then the positive electrode slurry is coated on the positive electrode collector and dried to form a positive electrode active layer on the positive electrode collector, and then a laser etching process is used to etch line grooves on the surface of the positive electrode active layer, thereby obtaining a positive electrode sheet. When using this method to prepare the positive electrode sheet, there is no special restriction on the solvent in the positive electrode slurry, as long as it can dissolve or disperse the above-mentioned components. Specifically, the solvent in the positive electrode slurry includes but is not limited to N-methylpyrrolidone (NMP), ethylene carbonate (EC), etc. In addition, when preparing the positive electrode sheet, the various components in the positive electrode active layer can also be dry mixed to form a sheet, and then the obtained sheet is crimped onto the positive electrode collector, and then a laser etching process is used to etch line grooves on the surface of the positive electrode active layer.

[0053] Negative electrode

[0054] In the negative electrode sheet, the components of the negative electrode active layer include negative electrode active materials, and the present application does not particularly limit the negative electrode active materials. Specifically, the negative electrode active material may include at least one of a carbon material or a silicon-based material. More specifically, the carbon material includes but is not limited to at least one of natural graphite, artificial graphite, mesophase microcarbon beads, hard carbon or soft carbon; the silicon-based material includes but is not limited to at least one of silicon, silicon-oxygen composite materials or silicon-carbon composite materials.

[0055] In some embodiments of the present application, the negative electrode active layer generally further contains a negative electrode conductive agent. The present application has no particular restrictions on the type of the negative electrode conductive agent, as long as the purpose of the present application can be achieved. For example, the negative electrode conductive agent includes but is not limited to at least one of acetylene black, Ketjen black, carbon nanotubes, carbon fibers, carbon dots or graphene.

[0056] In some embodiments of the present application, the negative electrode active layer may also contain a negative electrode binder and a thickener. The present application has no particular restrictions on the types of the negative electrode binder and the thickener, as long as the purpose of the present application can be achieved. For example, the negative electrode binder may include but is not limited to at least one of polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, styrene-butadiene rubber or acrylic (ester) styrene-butadiene rubber; the thickener in the negative electrode slurry may include but is not limited to at least one of sodium carboxymethyl cellulose or lithium carboxymethyl cellulose.

[0057] In the negative electrode sheet, the material of the negative electrode current collector includes but is not limited to copper foil, aluminum foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam or a polymer substrate covered with a conductive metal, etc., and there is no special limitation in this application. Among them, the conductive metal includes but is not limited to copper, nickel or titanium, and the material of the polymer substrate includes but is not limited to at least one of polyethylene, polypropylene, ethylene propylene copolymer, polyethylene terephthalate, polyethylene naphthalate or poly(p-phenylene terephthalamide).

[0058] In addition, in the present application, there is no particular limitation on the thickness of the negative electrode current collector and the negative electrode active layer, as long as the purpose of the present application can be achieved. For example, the thickness of the negative electrode current collector is 4 μm to 12 μm, and the thickness of the single-sided negative electrode active layer is 30 μm to 160 μm.

[0059] In addition, similar to the preparation of the positive electrode sheet, when preparing the negative electrode sheet, it can be configured into a negative electrode slurry, and then the negative electrode slurry is coated on the negative electrode collector and dried to form a negative electrode active layer on the negative electrode collector to obtain a negative electrode sheet; or the components in the negative electrode active layer can be dry mixed to form a sheet, and then the obtained sheet is crimped to the negative electrode collector to form a negative electrode active layer, thereby obtaining a negative electrode sheet. Of course, a laser etching process can also be used to etch grooves on the surface of the positive electrode active layer. The solvent in the negative electrode slurry includes any one of an aqueous solvent and an organic solvent. Aqueous solvents include but are not limited to a mixed solvent of alcohol and water or water. Organic solvents include, but are not limited to, aliphatic hydrocarbons such as hexane; aromatic hydrocarbons such as benzene, toluene, xylene, methylnaphthalene; heterocyclic compounds such as quinoline and pyridine; ketones such as acetone, methyl ethyl ketone, and cyclohexanone; esters such as methyl acetate and methyl acrylate; amines such as diethylenetriamine and N,N-dimethylaminopropylamine; ethers such as diethyl ether, propylene oxide, and tetrahydrofuran (THF); amides such as N-methylpyrrolidone (NMP), dimethylformamide, and dimethylacetamide; aprotic polar solvents such as hexamethylphosphoramide and dimethyl sulfoxide. In addition, in some other embodiments, when using an aqueous solvent, the components of the negative electrode slurry will also include a thickener and styrene-butadiene rubber (SBR) emulsion to slurry the negative electrode slurry, thereby adjusting the viscosity of the negative electrode slurry. The types of thickeners in the negative electrode slurry include, but are not limited to, at least one of carboxymethyl cellulose, methyl cellulose, hydroxymethyl cellulose, ethyl cellulose, polyvinyl alcohol, oxidized starch, phosphorylated starch, casein, and their salts.

[0060] In a third aspect, the present application provides a secondary battery, which includes an electrolyte, a separator, and pole pieces, wherein the separator and the pole pieces are alternately stacked; wherein the pole pieces are positive pole pieces and negative pole pieces alternately arranged.

[0061] In the secondary battery of the present application, the separator may be the separator of the first aspect, and the pole piece may be the pole piece of the second aspect. The separator of the first aspect and the pole piece of the second aspect may be used in the secondary battery alone or simultaneously. When used simultaneously, the cycle performance and fast charging performance of the secondary battery are more excellent.

[0062] In addition, when both are used in a secondary battery, the area between adjacent grooves in the pole piece is the bonding area, and the bonding point in the diaphragm is located in the bonding area. Since the bonding point in the diaphragm will not fall into the groove, the groove can play a good role in transmitting and storing electrolyte, which is conducive to further improving the cycle performance and fast charging performance of the secondary battery.

[0063] Electrolyte

[0064] The electrolyte can transport lithium ions and electrons to ensure the formation of a pathway inside the secondary battery. The electrolyte usually contains lithium salts, solvents and additives. It should be noted that the present application does not have any specific restrictions on the amount of each component in the electrolyte, as long as the purpose of the present application can be achieved.

[0065] Specifically, the lithium salt can be dissolved in a solvent to form an ion conductor, used as a conductive medium and a lithium ion transmission medium; the lithium salt includes but is not limited to at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(oxalatoborate), lithium bis(trifluoromethylsulfonylimide), lithium bis(fluorooxalatoborate), lithium bis(fluorosulfonylimide), and the like.

[0066] The solvent can dissolve the lithium salt and the additive, and the solvent can be at least one of carbonate, carboxylic acid ester, ether, alcohol, etc., wherein the carbonate can be divided into cyclic carbonate, linear carbonate, etc. Cyclic carbonate specifically includes but is not limited to at least one of ethylene carbonate, propylene carbonate, etc.; linear carbonate specifically includes but is not limited to at least one of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, etc.; carboxylic acid ester includes but is not limited to at least one of methyl formate, methyl acetate, methyl butyrate, ethyl propionate, propyl propionate, propyl acetate, etc.; ethers include but are not limited to at least one of tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, etc.; alcohols include but are not limited to at least one of ethanol, ethylene glycol, glycerol, etc.

[0067] The additives include, but are not limited to, nitriles, sulfones, sulfoxides, fluoronitriles, fluoroesters, and the like.

[0068] The secondary battery of the present application can be used in electronic devices, and the purpose of the electrochemical device of the present application is not particularly limited, and it can be used in any electronic device known in the prior art. In some embodiments, the electrochemical device of the present application can be used for, but not limited to, laptop computers, pen-input computers, mobile computers, e-book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.

[0069] Example

[0070] The following uses lithium-ion batteries as an example to provide examples and comparative examples to more specifically describe the implementation of the electrochemical device of the present application. Those skilled in the art will understand that the preparation method described in the present application is only an example, and any other suitable preparation method is within the scope of the present application.

[0071] Test methods and equipment:

[0072] Detection of bonding point quantity:

[0073] A Keyence VHX5000 CCD (Charge-coupled Device) electron microscope was used to observe the surface of the diaphragm at 100 times magnification and record the number of bonding points. Figure 1 2 is the CCD diagram of Example 1-5. It can be seen from the figure that the projection shape of the bonding point is a circular ring.

[0074] The bond points in a region are counted as follows:

[0075] For bonding points that are not fully displayed in the area, if the portion in the selected area is less than 50% of the entire bonding points, it will not be counted in the total number. If it is equal to or greater than 50%, it will be counted as one bonding point.

[0076] Electrolyte transfer rate test:

[0077] 1. Use the diaphragm or positive electrode as the object to be tested, and cut the sample to 15mm wide and 100mm long for later use;

[0078] 2. Fix both ends of the sample, leave the middle part hanging, and use a 1ml syringe to drop the electrolyte into the middle part of the sample (such as Figure 1 shown);

[0079] 3. Time for 1 minute and test the diffusion distance of the electrolyte along the length of the sample. Repeat three times for each sample and take the average value.

[0080] Fast charging performance test

[0081] Eight lithium-ion batteries of the same sample were placed in a low-temperature environment of 12°C and left to stand for 1 hour to allow the lithium-ion batteries to reach a constant temperature. The eight lithium-ion batteries were then divided into four groups, with two batteries in each group being tested. During the test, the four groups were cycled and discharged at 1.5C, 2C, 2.5C, and 3C, respectively. After the cycle was completed, the lithium batteries were disassembled, and the lithium plating window of the lithium-ion batteries was determined based on the purple spots produced on the negative electrode (i.e., anode) after comparison.

[0082] The specific steps of cyclic charge and discharge are as follows:

[0083] (1) Discharge at a constant current of 0.7C to 3.0V; (2) Let stand for 5 minutes; (3) Charge at a fixed rate and constant current to 4.5V, and then charge at a constant voltage to 0.05C; (4) Let stand for 5 minutes; (5) Repeat steps (1) to (4) 10 times.

[0084] In step (3), the fixed ratios are 1.5C, 2C, 2.5C, and 3C respectively.

[0085] In the test results, the higher the ratio of the lithium deposition window, the stronger the fast charging capability. Under the same ratio of the lithium deposition window, the milder the lithium deposition and the smaller the lithium deposition area, the stronger the fast charging capability. Specifically, the fast charging capability is ranked from worst to best as follows: severe lithium deposition on the entire anode surface < slight lithium deposition on the entire anode surface < severe lithium deposition in some parts of the anode < slight lithium deposition in some parts of the anode < slight lithium deposition on the anode < no lithium deposition on the anode.

[0086] Cyclic performance test

[0087] The lithium-ion battery was placed in a 45°C thermostat for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery was then discharged at a constant current of 0.2C to 3V, and then rested for 5 minutes to measure the initial discharge capacity C0 of the lithium-ion battery.

[0088] Then, charge and discharge were performed, where one charge and one discharge was counted as one cycle, and 800 cycles were performed. The discharge capacity C1 of the lithium-ion battery after 800 cycles was measured. The charging process is as follows: (1) 3.5C constant current charging to 4.35V; (2) 3C constant current charging to 4.35V, constant voltage charging to 1.8C; (3) 1.8C constant current charging to 4.4V, constant voltage charging to 1.5C; (4) 1.5C constant current charging to 4.53V, constant voltage charging to 1.2C; (5) 1.2C constant current charging to 4.58V, constant voltage charging to 2100mA; (6) sleep for 5 minutes; (7) 0.5C constant current charging to 4.53V, constant voltage charging to 0.05C. The discharge process is as follows: 0.7C constant current discharge to 3.0V.

[0089] The capacity retention rate after 800 cycles at 45°C = C1 / C0×100%.

[0090] The higher the capacity retention rate, the better the cycle performance of the lithium-ion battery.

[0091] Adhesion test

[0092] The national standard GB / T 2790-1995, that is, the 180° peel test standard is adopted to test the adhesion between the separator and the positive electrode or the negative electrode. The separator and the positive electrode or the negative electrode are cut into 54.2 mm × 72.5 mm samples, the separator and the positive electrode or the negative electrode are compounded, and hot pressing is performed using a hot press. The hot pressing conditions are: temperature 85°C, pressure 1 MPa, hot pressing time 85 s (seconds), the compounded samples are cut into 15 mm × 54.2 mm strips, and the adhesion between the separator and the positive electrode or the negative electrode is tested according to the 180° peel test standard.

[0093] Bond layer thickness test

[0094] The membrane sample was cut along the width direction of the membrane (the length direction is the winding direction of the battery cell, and the width direction is perpendicular to the length direction), and then tested with a scanning electron microscope. The thickness of the bonding layer in the area within 3mm in the width direction of the separator (overhang area) was measured, and 5 measurement points were taken, and the average value was calculated as the thickness of the bonding layer.

[0095] Example 1-1

[0096] <Preparation of Separator>

[0097] 90g of polymer particles (weight average molecular weight of 600,000, polymerized monomers are butadiene and methyl acrylate in a molar ratio of 1:1) are added to a stirrer, and then 10g of sodium carboxymethyl cellulose is added, and the mixture is stirred and mixed evenly. 5g of dimethylsiloxane as a wetting agent is added, and then deionized water is added and stirred, and the viscosity of the slurry is adjusted to 2000mPa·s to 5000mPa·s, and the solid content is 5%, and a bonding layer slurry is obtained. Subsequently, the above bonding layer slurry is evenly coated on both surfaces of the base film layer made of polyethylene by screen printing, and the coating weight is 0.4g / m 2 , and then dried in an oven, a bonding layer with a thickness of 3.2μm will be formed on the surface of the base film layer.

[0098] <Preparation of negative electrode sheet>

[0099] The negative electrode active materials artificial graphite, acetylene black, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 96:1:1.5:1.5, and then deionized water is added as a solvent to prepare a negative electrode slurry with a solid content of 70%, and then a vacuum mixer is used to stir evenly. The negative electrode slurry is evenly coated on one surface of a copper foil with a thickness of 8 μm, dried at 110°C, and cold pressed to obtain a negative electrode sheet coated with a 150 μm negative electrode active layer on one side, and then the above coating steps are repeated on the other surface of the copper foil to obtain a negative electrode sheet coated with a negative electrode active layer on both sides. The negative electrode sheet is cut into a specification of 74 mm × 867 mm and welded to the pole ear for standby use.

[0100] <Preparation of positive electrode sheet>

[0101] The positive electrode active materials of lithium cobalt oxide, acetylene black and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 75%, and then a vacuum mixer is used to stir evenly. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 12 μm, dried at 90°C, and cold pressed to obtain a positive electrode current collector coated with a positive electrode active layer with a thickness of H1 of 100 μm on one side, and then a laser is used to etch the surface of the positive electrode active layer along the length direction of the positive electrode active layer to form a groove, the width D1 of the groove is 0.2 mm, the spacing D2 between adjacent grooves is 1 mm, and the depth H2 of the groove is 10 μm; then the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active layer on both sides and provided with a groove. The positive electrode sheet was cut into a size of 74 mm×867 mm and the tabs were welded to the wide sides of the positive electrode sheet for later use. The grooves in the two positive electrode active layers were observed using a CCD electron microscope, and the projected area of ​​all the grooves on the current collector surface was measured to be 8%.

[0102] <Preparation of Electrolyte>

[0103] In an environment with a water content of less than 10ppm, non-aqueous organic solvents of ethylene carbonate (EC), diethyl carbonate (DEC), propylene carbonate (PC), propyl propionate (PP), and vinylene carbonate (VC) are mixed in a mass ratio of 20:30:20:28:2, and then lithium hexafluorophosphate (LiPF6) is added to the non-aqueous organic solvent to dissolve and mix evenly to obtain an electrolyte. Based on the total mass of the electrolyte, the mass content of LiPF6 is 8%.

[0104] <Preparation of lithium-ion batteries>

[0105] The positive electrode sheet, separator and negative electrode sheet prepared above are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and the bonding point in the separator does not fall into the groove of the positive electrode sheet, and then wound to obtain an electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, and the moisture is removed at 80°C, and the prepared electrolyte is injected. After vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.

[0106] Example 1-2 to Example 1-30

[0107] Except for adjusting the longest diameter of the bonding points, the distance between adjacent bonding points and the thickness of the bonding layer according to Table 1, the rest is basically the same as Example 1-1.

[0108] Example 1-31 to Example 1-42

[0109] Except for adjusting the thickness of the bonding layer in the positive electrode sheet and the parameters of D1 and D2 according to Table 1, the rest is basically the same as Example 1-29.

[0110] Comparative Example 1 to Comparative Example 16

[0111] Except for adjusting the parameters in the positive electrode plate and the separator according to Table 1, the rest is basically the same as Example 1-29.

[0112] The preparation method of the positive electrode sheet without the groove is as follows:

[0113] The positive electrode active materials lithium cobalt oxide, acetylene black, and polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 94:3:3, and then N-methylpyrrolidone (NMP) is added as a solvent to prepare a positive electrode slurry with a solid content of 75%, and then stirred evenly by a vacuum mixer. The positive electrode slurry is evenly coated on one surface of an aluminum foil with a thickness of 12μm, dried at 90°C, and cold pressed to obtain a positive electrode current collector coated with a positive electrode active layer with a thickness of H1 of 100μm on one side; then the above steps are repeated on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active layer on both sides. The positive electrode sheet is cut into a specification of 74mm×867mm and the wide side of the positive electrode sheet is welded with a pole ear for standby use.

[0114] In addition, when preparing the diaphragm, the bonding layer slurry is coated in a dot matrix coating manner, so that there are no discontinuous bonding points in the bonding layer.

[0115] Table 1

[0116]

[0117]

[0118]

[0119]

[0120] Example 2-1 to Example 2-5

[0121] Except for adjusting the type of aqueous polymer in the separator and D1 and D2 in the negative electrode plate according to Table 2, the rest is basically the same as Example 1-35.

[0122] Table 2

[0123]

[0124] Note: In Table 2, the "longest diameter of the bonding point", "distance between adjacent bonding points" and "bonding layer thickness" in Examples 2-1 to 2-5 are the same as those in Example 1-35, and therefore are not described in Table 2.

[0125] Example 3-1 to Example 3-14

[0126] Except for adjusting the parameters of the negative electrode plate according to Table 3, the rest is basically the same as Example 1-35.

[0127] Table 3

[0128]

[0129]

[0130] It can be seen from the table that when the secondary battery of the present application meets the scope limited by the present application, the cycle performance and fast charging performance of the secondary battery can be improved. In particular, when the longest diameter of the bonding point is 10μm~200μm, or the distance between adjacent bonding points is 150μm~300μm, the cycle performance and fast charging performance of the secondary battery are better; in particular, when the range of 0.1≤H2 / H1 in the negative electrode sheet is 0.1~0.3, or the projected area of ​​the groove on the collector surface is 10%~20% of the collector surface area, the cycle performance and fast charging performance of the secondary battery are better. In addition, the test results of the electrolyte transmission rate show that the electrolyte transmission rate is positively correlated with the cycle performance and fast charging performance of the secondary battery.

[0131] It should be noted that, in this article, the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method or article that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements that are inherent to such process, method or article.

[0132] Each embodiment in this specification is described in a related manner, and the same or similar parts between the embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0133] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.

Claims

1. A secondary battery, comprising a separator and a pole piece, characterized in that: The diaphragm comprises a base film layer, at least one surface of the base film layer is provided with a bonding layer, the bonding layer is composed of a plurality of bonding points, the thickness of the bonding layer is 0.5 μm to 5 μm; in the bonding layer, the longest diameter of the bonding points is 10 μm to 400 μm, and the distance between adjacent bonding points is 100 μm to 400 μm; The pole piece includes a current collector, at least one surface of which is provided with an active layer, a surface area of ​​the active layer is partially recessed inward to form a plurality of grooves, and the grooves are arranged along the length direction of the pole piece; the width of the grooves is D1mm, 0.2≤D1≤1.

5.

2. The secondary battery according to claim 1, characterized in that: The longest diameter of the bonding points is 10 μm to 200 μm; and / or the distance between adjacent bonding points is 150 μm to 300 μm.

3. The secondary battery according to claim 1 or 2, characterized in that: The thickness of the bonding layer is 1 μm to 3 μm.

4. The secondary battery according to claim 1, characterized in that: The adhesive layer includes a water-based polymer, and the polymerized monomers of the water-based polymer include at least two of butadiene, acrylate, styrene, methacrylate, ethylene, propylene or vinylidene fluoride.

5. The secondary battery according to claim 1, characterized in that: The thickness of the active layer is H1 μm, the depth of the groove is H2 μm, and 0.1≤H2 / H1≤0.

3.

6. The secondary battery according to claim 1, characterized in that: The projection area of ​​all the scored grooves on the surface of the current collector is 10% to 20% of the surface area of ​​the current collector.

7. The secondary battery according to claim 1, characterized in that: The pole piece is a negative pole piece.

8. The secondary battery according to claim 1, characterized in that: The spacing between adjacent scored grooves is D2 mm, 1≤D2≤3.

9. The secondary battery according to claim 1, characterized in that: The area between adjacent score grooves is a bonding area, and the bonding point is located in the bonding area.

10. An electronic device, characterized in that: It comprises the secondary battery according to any one of claims 1 to 9.

Citation Information

Cited By

  • Separator and secondary battery

    WO2026056935A1

  • Separator and secondary battery

    WO2026056973A1

  • Secondary battery and electronic apparatus

    WO2026123756A1